Blood from the tube –cultivation of red cells in vitro - Primož Poženel (Zdravniški Vestnik, 2014)
Red cell transfusion is an established mode of therapy. Growing demand for red cell concentrates due to ageing population will in the next decades drive the introduction of new approaches in blood supply. In vitro red cell culturing is one of them. This technology enables us to yield red cells from various hematopoietic stem cells. The main goal is to gain large quantities of mature enucleated red cells expressing adult hemoglobin that are of »universal blood group« 0 RhD- negative and compatible with respect to the other blood group systems. At the moment, the technology efficiency does not allow the production of large amounts of red cells that could be comparable to blood donation gains. The majority of in vitro protocols is based on expansion from umbilical cord blood. Promising sources of stem cells are induced pluripotent stem cells (iPSCs) and human embryonic stem cells, which are still questionable due to their tumorigenicity. The first transfusion of a small volume of in vitro autologous red cells has already been performed. Despite certain shortcomings of in vitro erythropoiesis, we are not far from routine use of red cells that are produced in a laboratory.